The Effects of Social Comparison and Objective Feedback on Work Performance Across Different Performance Levels. Issue 1 (2nd January 2017) - Moon, Kwangsu; Lee, Kyehoon; Lee, Kyounga; Oah, Shezeen
ABSTRACT: This study investigated the interaction effects of feedback content type (social comparison feedback vs. objective feedback) and two different performance levels (high vs. low) on work performance. One hundred fifty participants were recruited and asked to perform a simulated work task in a preliminary session. Based on their performance, the upper 40% (high performance) and lower 40% (low performance) groups were selected for the main experiment. Participants in each group were randomly assigned to the two different experimental conditions: objective feedback and social comparison feedback. For the participants in the objective feedback condition, information on the number of correctly completed work tasks was provided. For the participants in the social comparison feedback condition, rank information on their performance was provided. The results indicated that social comparison feedback was more effective than objective feedback for the high performers, but was less effective for the low performers.